Indonesian EFL Nursing Students’ Learning Process: Obstacles & Expectations - Gilang Rajasa (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2018)
Nursing students learn English language as specific purposes (ESP). They should be able to learn do communication in English to be a professional nurse. However, learning English was not an easy game to do. There will be some difficulties and adjustment along the learning process. Thus, the research is aimed at. A descriptive qualitative methodology as the foundation to investigate the obstacles in the learning process among Indonesian EFL nursing students and to examine the nursing students’ expectation in English learning process. Open-ended questionnaire and semi-structured interview would be the instruments to gain support some information. About 24 respondents and 3 of representatives of 7th semester nursing students would be the respondents. The result showed that besides grammar, structure, and tenses application, four skills implementation, lecturer’s effects, and institution’s regulations (curriculum management distribution, time schedule management, connection problem between staffs authority and lecturer) would be the major obstacles. Meanwhile, better communication among nursing institute stakeholders about schedule, time management, curriculum and modifying classroom activities could be the better expectation emerged to reduce the EFL nursing students’ obstacles. This research concluded that adjusting the regulation for the English subject curriculum and altering nursing students to encourage and motivate themselves to learn about English could change the outcome and situation to build pedagogical implication and to plan more comprehensive English learning activities.